Combination of collocation and factorization methods applied to numerical solutions of bubble-inside drop system dynamics - Hai, Duong Ngoc (Vietnam Journal of Mechanics, 1999)
In the paper the combination of collocation and factorization methods applied to numerical investigation of bubble-inside drop system dynamics is presented. Initially assumed bubble and drop have ellipsoidal forms. The initial relative location of the drop in the bubble is determined by equilibrium condition between drop weight and lift-force due to pressure distribution in gas/vapor. Calculations are implemented for the case of spherical bubble, drop without and with vaporization (thermal effect) and for the experimental case [6] with alumina drop in water in pressure waves.